Islamic Fintech Development Strategy in Indonesia: Analytic Network Process (ANP) Approach - Surbakti, Mhd Handika; Nurzaman, Mohamad Soleh (SMART Insight, 2024)
This study aims to analyze problem priorities, solutions and strategies in the development of Islamic fintech in Indonesia by using Analytical Network Process (ANP) method. The background of this study is the rapid growth of the Islamic fintech industry in Indonesia, but until now the map has not been found in its development. This study involved stakeholders from the government/ regulators, practitioners and academics as the research respondents. The results of this study showed that the problem priorities of Islamic fintech development in Indonesia respectively are Regulation, Literacy, Human Resources (HR) and Capital. While the solution priorities respectively are Literacy, Human Resources (HR), Regulation and Capital. The alternative priorities for the Islamic fintech development strategy in Indonesia respectively are Increasing Literacy, Strengthening Government Support, Improving Quality and Quantity of Human Resources (HR), Expanding Access to Capital and Creating Ecosystems. This study shows that collaborative efforts are needed so that the Islamic fintech industry in Indonesia can develop and be sustainable.